Reduced SERCA Function Preferentially Affects Wnt Signaling by Retaining E-Cadherin in the Endoplasmic Reticulum. - Suisse, A.; Treisman, J.E. (Cell reports, 2019)
Calcium homeostasis in the lumen of the endoplasmic reticulum is required for correct processing and trafficking of transmembrane proteins, and defects in protein trafficking can impinge on cell signaling pathways. We show here that mutations in the endoplasmic reticulum calcium pump SERCA disrupt Wingless signaling by sequestering Armadillo/?-catenin away from the signaling pool. Armadillo remains bound to E-cadherin, which is retained in the endoplasmic reticulum when calcium levels there are reduced. Using hypomorphic and null SERCA alleles in combination with the loss of the plasma membrane calcium channel Orai allowed us to define three distinct thresholds of endoplasmic reticulum calcium. Wingless signaling is sensitive to even a small reduction, while Notch and Hippo signaling are disrupted at intermediate levels, and elimination of SERCA function results in apoptosis. These differential and opposing effects on three oncogenic signaling pathways may complicate the use of SERCA inhibitors as cancer therapeutics.